2022
DOI: 10.1021/acs.biochem.2c00565
|View full text |Cite
|
Sign up to set email alerts
|

Inter-domain Flexibility of Human Ser/Arg-Rich Splicing Factor 1 Allows Variable Spacer Length in Cognate RNA’s Bipartite Motifs

Abstract: Ser/Arg-rich splicing factor 1 (SRSF1 or ASF/SF2) is the prototypical member of SR proteins. SRSF1 binds to exonic splicing enhancers, which prompts inclusion of corresponding exons in the mature mRNA. The RNA-binding domain of SRSF1 consists of tandem RNA-recognition motifs (RRM1 and RRM2) separated by a 30 amino acid long linker. In this study, we investigate roles of RRM1, RRM2, and the linker in RNA binding. We find that although both RRMs are crucial to RNA binding, RRM2 plays the dominant role. The linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Others and our studies have identified the SRSF1 residues for RNA binding, such as Y19, F56, F58, W134, and Q135 (Fig. 3A) (26,28). In our previous study, we have confirmed that mutation of these residues does not perturb the protein structure (28).…”
Section: Identification Of Key Srsf1 Residues Responsible For Arpc2 G...supporting
confidence: 73%
See 2 more Smart Citations
“…Others and our studies have identified the SRSF1 residues for RNA binding, such as Y19, F56, F58, W134, and Q135 (Fig. 3A) (26,28). In our previous study, we have confirmed that mutation of these residues does not perturb the protein structure (28).…”
Section: Identification Of Key Srsf1 Residues Responsible For Arpc2 G...supporting
confidence: 73%
“…3A) (26,28). In our previous study, we have confirmed that mutation of these residues does not perturb the protein structure (28). Therefore, we compared binding affinities of the wild-type RRM tandem with its mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These motifs are also present in ARPC2 GQ. Others and our studies have identified the SRSF1 residues for RNA binding, such as Y19, F56, F58, W134 and Q135 (Figure 3A and B ) ( 26 , 28 ). In our previous study, we have confirmed that mutation of these residues does not perturb the protein structure ( 28 ).…”
Section: Resultsmentioning
confidence: 62%
“…RRM1 prefers C-containing RNA motifs ( 25 ), while RRM2 prefers GGA motifs ( 26 , 27 ) (Figure 1A ). Consequently, SRSF1’s RRM tandem recognizes purine-rich RNA motifs with upstream or downstream C motifs ( 25 , 28 ). Unlike SRSF1, SRSF3’s RRM recognizes pyrimidine-rich RNA sequences ( 29 ).…”
Section: Introductionmentioning
confidence: 99%